Diversifying local diets: nutrition education for mothers/caregivers improved the diversity of complementary foods of children in Western Kenya - Keding, G.B.; Waswa, Lydiah M. (Bioversity International, 2015)
Malnutrition among children under 5 years is still a widespread problem in many developing countries. While consuming a variety of foods is important for meeting essential nutrient requirements, traditional diets fed to children in many developing countries are based predominantly on starchy staples with few or no nutrient-rich foods such as fruits, vegetables and animal source foods. To understand the use of local agricultural biodiversity in diets, nutrition surveys were carried out at the household level to understand the current composition of the diet and its nutritional value. Nutrition education was targeted to mothers and caregivers in half of the 40 villages that participated in the project by working closely with local community health workers. Results showed that nutrition education led to an increase in the diversity of children’s diets and that it was possible to improve the quality of the diet using combinations of locally available foods.